"Do I feel threatened? No… I'm learning!"—Affective and relational dynamics in science professional development. Issue 2 (31st December 2018) - Finkelstein, Carla; Jaber, Lama Z.; Dini, Vesal
Abstract: This paper focuses on interactions in a science professional development (PD) course in which participating teachers engaged in doing science. Whereas the PD design of this course aligned with research on effective PD practices, we found that these practices did not sufficiently account for the affective and relational dynamics that unfolded in the PD interactions. In this paper we explore how critical discourse analysis (CDA) can be used both to theorize and analyze the affective and relational work happening in PD, through the critical lenses of power and positioning. Our analysis surfaces tensions between participants and facilitators, as well as among participants, which often related to their notions of disciplinary expertise. More important, our analysis shows that attunement to affective and relational dynamics, including explicit attention to communication norms, is essential for engendering productive learning opportunities within PD spaces. We discuss the implications of this study for teacher educators and PD facilitators, and we end with directions for future research on affective and relational dynamics in teacher learning.